Building a Digital Literacy Embankment: Effective Strategies for Facing Online Challenges at SD Negeri 2 Tirtasari, Buleleng - Pratiwi, Ni Komang Desi; Cahyanti, Putu Juwita; Kadek Tasya Wiryantini; Nicanta, Flower; Darmika, I Made Punia; Maharani, Putu Ananda Febry; Werang, Basilius Redan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to identify effective strategies in building digital literacy to face online challenges in elementary schools. Using qualitative methods, data was collected through interviews, classroom observations, and surveys of teachers, students, and parents. The research results show that the integration of digital literacy in the curriculum, ongoing training for teachers, and improving technology access and infrastructure significantly improve students' digital understanding and skills. These findings show active participation from various parties. No significant differences were found in the effectiveness of this strategy based on student gender or grade, indicating universal and inclusive application. Thus, this research highlights the importance of collaboration between schools and families and the provision of adequate resources to create an optimal and inclusive digital learning environment for all students.